2020
DOI: 10.1002/anie.202000108
|View full text |Cite
|
Sign up to set email alerts
|

Design of Turn‐On Near‐Infrared Fluorescent Probes for Highly Sensitive and Selective Monitoring of Biopolymers

Abstract: Simple, sensitive, and selective detection of specific biopolymers is critical in a broad range of biomedical and technological areas. We present a design of turn-on nearinfrared (NIR) fluorescent probes with intrinsically high signal-to-background ratio. The fluorescent signal generation mechanism is based on the aggregation/de-aggregation of phthalocyanine chromophores controlled by selective binding of small-molecule "anchor" groups to a specific binding site of a target biopolymer. As a proof-of-concept, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…In the presence of nanomolar concentrations of EGFR kinase, the anchor’s selective binding to the target kinase causes partial deaggregation of the ZnPc fluorophore and generation of near-IR fluorescent emission in a concentration-dependent manner. At the same time, sensor 1 does not show nonselective binding and displays no fluorescent response to other biomacromolecules . Despite the promising performance of 1 in cell-free environments, the transition to cellular imaging encountered major obstacles.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the presence of nanomolar concentrations of EGFR kinase, the anchor’s selective binding to the target kinase causes partial deaggregation of the ZnPc fluorophore and generation of near-IR fluorescent emission in a concentration-dependent manner. At the same time, sensor 1 does not show nonselective binding and displays no fluorescent response to other biomacromolecules . Despite the promising performance of 1 in cell-free environments, the transition to cellular imaging encountered major obstacles.…”
Section: Resultsmentioning
confidence: 99%
“…First, we found that 1 was insufficiently water-soluble. Indeed, the in vitro target response experiments required an aqueous medium with 10% DMSO to produce a fluorescent signal . Such conditions are obviously not ideal (if even achievable) for live-cell imaging.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using smart near-infrared (NIR) fluorescence imaging probes constructed from organic molecules to target specific cellular organelles is an emerging field of contemporary research . NIR fluorescent biomarkers (650–900 nm) for intracellular locations are indispensable in contrast with visible and other fluorescent dyes because NIR light can permeate deep tissues and offers a meaningful bioimaging method with negligible autofluorescence background . Mitochondria are crucial targets within the numerous cellular organelles .…”
mentioning
confidence: 99%